Analisis Sistem Informasi Akuntansi Penggajian Dan Pengupahan Dalam Meningkatkan Efektivitas Pengendalian Internal Pada My Bunda Collection - Heriyanto Heriyanto; Dwi Yuniarti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Task and responsibility overlap, salary and wage calculation errors, and an unintegrated system are issues in the payroll process at the company. The ineffectiveness of the payroll and remuneration accounting information system can affect employee welfare and the development of a company. This research aims to understand the payroll and wage accounting information system at My Bunda Collection and to determine whether the implemented system effectively supports internal control efforts. The qualitative method was carried out using primary data sources obtained through direct interviews, as well as secondary data collected from relevant records or supporting documents. The research results indicate that the implementation of the payroll and wage accounting information system at My Bunda Collection is quite good, although it does not yet align with the theory of payroll and wage accounting information systems. This is seen from the lack of records and documents supporting the payroll and wage processes, as well as the occurrence of task and responsibility overlaps. However, the system in place is quite effective in supporting the company's internal control efforts, as evidenced by the authorization of employee pay slips by the company's CEO to verify the accuracy of the salaries and wages to be disbursed by the company.